ANALISIS NILAI PENDIDIKAN KARAKTER DALAM DONGENG KUPU-KUPU INDAH YANG SOMBONG KARYA YOGA TRIANA - Rouli Simanullang; Sitorus, William T; Widya Octavianty; Fitriani Lubis (FKIP, Universitas Palangka Raya, 2023)
The purpose of this study was to examine educational values ​​in the form of quotations from the fairy tale